A comparison of traditional versus electronic word of mouth as marketing tools / Ramli Saad and Rosliza Md Zani - Saad, Ramli; Md Zani, Rosliza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Traditionally, the word of mouth (WOM) is taking place through spoken communication shared in a face to face context involving two parties. It is characterized by its synchronicity and the relatively short delay in word and response exchange. Word of mouth can influence consumers to make a decision making, representing the interpersonal influence between sender and receiver, whether positively or negatively influencing the recipient's attitudes (Yang 2017). This can be contributed to the recei ver's perception of the sender's neutrality, increasing the perception of reliability of the message above any company communications.